Type Of Slang Found In American Gangster Move Directed By Ridley Scott - Putra, Ngakan Putu Ditya Suadirja (Journal of Linguistics, Literacy, and Pedagogy, 2024)
This study entitled Type of Slang Found in American Gangster Move Directed by Ridley Scott. The aim of study is to identify the types of Slang word used in the movie. The Qualitative method is used on this study. There were several steps taken in collecting the data such as: watching the movie, reading the movie script and understanding the words, phrases and dialogues by taking a noted of the data found, identifying and classifying the data based on the type of slang words found on the movie. The writer uses the theory from Eric Partridge (1945) on the book of “Slang To-Day and Yesterday”. The study concludes that 15 slang words are found in the movie such as: shit, asshole, fuck, nuts, my man, cool, junkie, baby, bullshit, motherfucker, what the hell, bro, fellas, guys and dough. Based on the research results, the most widely used type of slang is society slang.